2008
DOI: 10.1002/jmv.21171
|View full text |Cite
|
Sign up to set email alerts
|

A part of the VP4 capsid protein exhibited by coxsackievirus B4 E2 is the target of antibodies contained in plasma from patients with type 1 diabetes

Abstract: The capsid protein VP4 was identified previously as the target of antibodies contained in plasma enhancing the coxscakievirus B4 (CV-B4) E2-induced production of IFN-alpha by peripheral blood mononuclear cells (PBMCs). The sequence of VP4 recognized by these antibodies was investigated. This sequence was identified as amino acids 11 to 30 by using synthetic overlapping peptides spanning VP4(CV-B4 E2) in competition experiments for antibodies enhancing the CV(B4 E2) induced production of IFN-alpha by PBMCs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…These polyclonal antibodies demonstrated a strong reaction to the peptides corresponding to the N termini of VP1 and VP3 of swine vesicular disease virus and coxsackievirus A9, respectively. In a similar study, antibodies from the plasma of patients suffering from type I diabetes were found to target VP4 protein of coxsackievirus B3, again suggesting the exposure of VP4 peptide during coxsackievirus infection (23). These results imply that capsid "breathing" may be a phenomenon common to many proteinaceous capsids.…”
mentioning
confidence: 73%
“…These polyclonal antibodies demonstrated a strong reaction to the peptides corresponding to the N termini of VP1 and VP3 of swine vesicular disease virus and coxsackievirus A9, respectively. In a similar study, antibodies from the plasma of patients suffering from type I diabetes were found to target VP4 protein of coxsackievirus B3, again suggesting the exposure of VP4 peptide during coxsackievirus infection (23). These results imply that capsid "breathing" may be a phenomenon common to many proteinaceous capsids.…”
mentioning
confidence: 73%
“…The Swiss-Pdb Viewer is used to evaluate the predicted structure. The Ramachandran plot (bottom, right) shows how good the values of the dihedral angles agree with the values of allowed conformations themenschwerpunkt SWISS-MODEL, ranging from mutations, chimeric enzymes to active sites and factor-receptor complexes [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. The resulting structures can be visualized at the Pdb-Viewer in several representations such as balls-and-sticks or as ribbon (showing secondary structure elements) and the molecular surface can be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have recently demonstrated that the VP4 protein and the plasma-isolated anti-VP4 antibodies play an important role in the enhancement of PBMC infection by CV-B4 [92]. The VP4 target amino-acid sequence implied in this antibody-dependent IFNa enhancement was determined, and it was noted that antibodies directed against VP4 or peptides of VP4 are more prevalent and at higher rates in type 1 diabetic patients than in control subjects [93]. In addition, these results show that the VP4 protein is accessible to antibodies at 378C, which suggests that the conformation of the viral particle at physiological temperatures is different from that deduced from the data obtained by X-ray diffraction of frozen viruses, in which the whole VP4 is inside the capsid.…”
Section: Antibody-dependent Enterovirus Infectionmentioning
confidence: 98%